The background levels of heavy metal concentration in sediments of the west coast of Peninsular Malaysia - Ismail, Ahmad; Badri, M.A.; Ramlan, Mohd Noor (Elsevier, 1993)
The west coast of Peninsular Malaysia is exposed to several sources of pollutants, predominantly from human activities. In this study heavy metal contamination was studied in the sediments collected from sampling stations all along the west coast of Peninsular Malaysia. The results show that in general the background levels of heavy metals in the sediments in most of the stations are still within the normal levels found elsewhere. Over 70% of Fe analysed ranges between 25000–50000 μg/g, over 50% of Mn analysed ranges from 3,000 to 5,000 μg/g. The bulk of Zn (60%) analysed ranges from 600 to 900 μg/g and over 70% of Pb analysed in sediments falls within 10–30 μg/g. Cu analysed shows over 70% below 5 μg/g, while for Cd over 80% is below 1 μg/g. The usefulness of the background concentrations is justified in view of the expected increases in industrial, domestic and municipal effluents discharged as the country makes headway into diversified land-based developments, especially in the industrial sector. This is especially so along the western coasts of Peninsular Malaysia, where over 70% of the populations live. The anthropogenic input of heavy metals into the coastal environment of Peninsular Malaysia had not been adequately studied; however, there are valid reasons to suspect increasing amounts of heavy metals in the coastals sediments.